Atopic Dermatitis-Related Inflammation in Macrophages and Keratinocytes: The Inhibitory Effects of Bee Venom - Deok-Hyun Kim; Ho-Sueb Song (MEDrang Inc., 2019)
Background This study investigated the anti-inflammatory effects of bee venom (BV) through the inhibition of nuclear factor kappa beta (NF-κB) expression in macrophages and keratinocytes. Methods Cell viability assays were performed to investigate the cytotoxicity of BV in activated macrophages [lipopolysaccharide (LPS)] and keratinocytes [interferon-gamma/tumor necrosis factor-alpha (IFN-γ/TNF-α)]. A luciferase assay was performed to investigate the cellular expression of NF-κB in relation to BV dose. The expression of NF-κB inhibitors (p-IκBα, IκBα, and p50 and p65) were determined by Western Blot analysis, and the electromobility shift assay. A nitrite quantification assay was performed to investigate the effect of BV, and NF-κB inhibitor on nitric oxide (NO) production in macrophages. In addition, Western Blot analysis was performed to investigate the effect of BV on the expression of mitogen-activated protein kinases (MAPK) in activated macrophages and keratinocytes. Results BV was not cytotoxic to activated macrophages and keratinocytes. Transcriptional activity of NF-κB, and p50, p65, and p-IκBα expression was reduced by treatment with BV in activated macrophages and keratinocytes. Treatment with BV and an NF-κB inhibitor, reduced the production of NO by activated macrophages, and also reduced NF-κB transcriptional activity in activated keratinocytes (compared with either BV, or NF-κB inhibitor treatment). Furthermore, BV decreased p38, p-p38, JNK, and p-JNK expression in LPS-activated macrophages and IFN-γ/TNF-α-activated keratinocytes. Conclusions BV blocked the signaling pathway of NF-κB, which plays an important role in the inflammatory response in macrophages and keratinocytes. These findings provided the possibility of BV in the treatment of atopic dermatitis.